A novel method for measuring asymmetry in kinematic and kinetic variables: The normalized symmetry index. (23rd January 2020) - Queen, Robin; Dickerson, Laura; Ranganathan, Shyam; Schmitt, Daniel
Abstract: Gait and movement asymmetries are important variables for assessing locomotor mechanics in humans and other animals and as a predictor of injury risk and success of clinical interventions. The four indices used most often to assess symmetry are not well designed for different variable types, perform poorly when presented with cases of high asymmetry or when variables are of low magnitude, and are easily influenced by small variation in the signal. The purpose of the present study was to test the performance of these indices on previously unpublished data on ACL-R patients and to propose a new index to resolve some of these limitations. The performance of four currently used indices and a new index—the Normalized Symmetry Index (NSI), which is scaled to the range of variables being tested across multiple trials—were compared using force and angular data on participants who had undergone anterior cruciate ligament reconstruction and healthy controls. The NSI performed well compared to all other indices with all variables and had the additional benefit of returning values that range from 0% (full symmetry) to ±100% (full asymmetry). Therefore, the NSI can serve as a universal index for assessing asymmetry in humans, nonhuman animal models, and in a clinical context for assessing risk for injury and clinical outcomes.